2021
DOI: 10.1016/j.isci.2021.103434
|View full text |Cite
|
Sign up to set email alerts
|

STING regulates peripheral nerve regeneration and colony stimulating factor 1 receptor (CSF1R) processing in microglia

Abstract: Summary Inflammatory responses are crucial for regeneration following peripheral nerve injury (PNI). PNI triggers inflammatory responses at the site of injury. The DNA-sensing receptor cyclic GMP-AMP synthase (cGAS) and its downstream effector stimulator of interferon genes (STING) sense foreign and self-DNA and trigger type I interferon (IFN) immune responses. We demonstrate here that following PNI, the cGAS/STING pathway is upregulated in the sciatic nerve of naive rats and dysregulated in old rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…The gene Nlrp3 is a key player in inflammasome formation, which contributes to neuroinflammation and cell death [66,67]. The genes Mb21d1 and Tmem173 encode two key proteins in the cGAS/STING pathway of the innate immune response, which has been shown to be activated in the microglia of the spinal cord after sciatic nerve injury [68]. Furthermore, several genes (Apoe, Blnk, and autophagy-related genes Lamp1, Pink1) were found to be downregulated in SCI/Becn1 +/mice compared to SCI/WT animals.…”
Section: Discussionmentioning
confidence: 99%
“…The gene Nlrp3 is a key player in inflammasome formation, which contributes to neuroinflammation and cell death [66,67]. The genes Mb21d1 and Tmem173 encode two key proteins in the cGAS/STING pathway of the innate immune response, which has been shown to be activated in the microglia of the spinal cord after sciatic nerve injury [68]. Furthermore, several genes (Apoe, Blnk, and autophagy-related genes Lamp1, Pink1) were found to be downregulated in SCI/Becn1 +/mice compared to SCI/WT animals.…”
Section: Discussionmentioning
confidence: 99%
“…This inflammatory response is characterized by secretion of IL-10 and TGF-, polarization of macrophages to an M2 subtype, and infiltration of Tregs 44,46,[74][75][76][77] all are known suppressors of anti-tumoral immunity. The degraded myelin fragments are known damage-associated molecular patterns (DAMPs) molecules, capable of stimulating an IFN-I response by cells in the peri-neural niche 78 . In parallel to the continuous damage inflicted by cancer cells, the IFN-I signaling by itself can propagate the nerve degeneration process [79][80][81] and promote the cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, activating IFN-I/IFNAR signaling suppressed sodium channel and calcium channel activity (95). However, it has been observed that STING1 can be expressed in macrophages, microglia, and the spinal cord after PNI and spinal cord injury (96,97), raising the possibility that the effects of STING1 may go beyond its actions with DRG sensory neurons.…”
Section: Primary Sensory Neurons: Driving Stimulus-evoked Painmentioning
confidence: 99%